Prenatal allergic sensitization to helminth antigens in offspring of parasite-infected mothers. - Weil, G J (1983)
Total and filaria-specific immunoglobulin E (IgE) levels were studied in cord blood from infants born in Madras, India, where filariasis and intestinal helminth infections are highly endemic. Increased total IgE levels were observed in 82% of 57 cord sera tested (geometric mean 12.6 ng/ml; range 1-1,900 ng/ml). 33 of these sera also contained IgE antibodies specific for filarial antigens as determined by solid-phase radioimmunoassay. Comparison of ratios of filaria-specific IgE to total IgE in paired maternal and cord sera suggested that cord blood IgE was derived from the fetus in most cases and not from transplacental antibody transfer. Our results suggest that prenatal allergic sensitization to helminth parasites occurs in the tropics. Such sensitization may contribute to the heterogeneity in host immune response and disease expression noted in filariasis and other helminth infections.